Computers and the hip arthroplasty operating room - Cobb,J; Harris,S; Clarke,S (2014)
In the arthroplasty market, globally sales and marketing strategies continue to have a dominantimpact on prosthesis choice.If the promise of the patient-matched technology is born out, then the next generation ofsmaller, more patient-friendly devices, inserted using patient-matched instrumentation, may becost neutral with the conventional prostheses inserted conventionally, by reducing theinventory and instrumentation needed per case.As the patient-matched procedures gather momentum, their low cost, in both time and money,will transform the industry.The artisan hip surgeon will still perform his or her trade using those few tools that Charnleydeveloped.In the operating room, the anesthetist may well have computers monitoring every organsystem, but the surgeon, in all likelihood, will have a great deal of computer-based knowledgewrapped up in a US$25 piece of polymer that embodies the plan that the patient agreed topreoperatively. That is a world beyond computers, and it is happening now